Education fund planning: awareness on insurance education plan / Badrul Hisyam Ahmad Fadalullah - Ahmad Fadalullah, Badrul Hisyam (Faculty of Business and Management, 2010)
It cannot be denied that the cost of education has increased tremendously in the past years. Most parents want the best education for their children and have started to plan for their children’s education from the time the children are infant. Since the number of public universities is limited, parents have no choice but to enrol their children in private universities are very costly .Therefore; the research is conducted to study the level of consumer awareness towards education fund planning especially with Insurance Education Plan.